Analysis of Differences in Organizational Commitment Among Civil Servants of Generation X, Generation Y, and Generation Z - Adi Wadjdi; Edi Setiawan; Tatan Sukwika (Journal Research of Social Science, Economics, and Management, 2026)
This research aims to empirically analyze the differences in organizational commitment in terms of affective, sustainable, and normative dimensions in the State Civil Apparatus (ASN) of the three generations. This case study was conducted at the Deputy for Apparatus Administration, Ministry of State Secretariat, a strategic work unit that provides technical and administrative support and analysis to the President and Vice President. This study used a comparative quantitative approach with a cross-sectional design and survey method using Meyer and Allen's Three Component Model (TCM) instrument. A sample of 129 respondents was selected through a non-proportionate stratified random sampling technique to ensure adequate representation of each generation. Given that the research data were not normally distributed, hypothesis analysis was carried out using the Kruskal-Wallis non-parametric test. The results of descriptive analysis show that all three dimensions of organizational commitment are in the high category, with affective commitment recording the highest score. However, the results of statistical tests showed that there were no statistically significant differences (p>0.05) in the three dimensions of organizational commitment -affective, continuance, and normative- among Generation X, Y, and Z ASNs. The main conclusion of this study is that in the context of the research locus, the generational factor is not a significant differentiating variable for the level of organizational commitment. The strong influence of organizational culture, job stability, and the strategic nature of tasks within the Ministry of State Secretariat proved to be more dominant in shaping commitments that tend to be homogeneous across generations.